A controlled examination of acute warning signs for suicide attempts among hospitalized patients - Bagge, Courtney L.; Littlefield, Andrew K.; Wiegand, Timothy J.; Hawkins, Eric; Trim, Ryan S.; Schumacher, Julie A.; Simons, Kelsey; Conner, Kenneth R. (Psychological medicine, 2023)
Near-term risk factors for suicidal behavior, referred to as 'warning signs' (WS), distinguish periods of acute heightened risk from periods of lower risk within an individual. No prior published study has examined, using a controlled study design, a broad set of hypothesized WS for suicide attempt. This study addressed this gap through examination of hypothesized behavioral/experiential, cognitive, and affective WS among patients recently hospitalized following a suicide attempt. Participants were recruited during hospitalization from five medical centers across the USA including two civilian hospitals and three Veterans Health Administration facilities ( = 349). A within-person case-crossover study design was used, where each patient served as her/his own control. WS were measured by the Timeline Follow-back for Suicide Attempts Interview and were operationalized as factors that were present ( absent) or that increased in frequency/intensity within an individual during the 6 h preceding the suicide attempt (case period) compared to the corresponding 6 h on the day before (control period). Select WS were associated with near-term risk for suicide attempt including suicide-related communications, preparing personal affairs, drinking alcohol, experiencing a negative interpersonal event, and increases in key affective (e.g. emptiness) and cognitive (e.g. burdensomeness) responses. The identification of WS for suicidal behavior can enhance risk recognition efforts by medical providers, patients, their families, and other stakeholders that can serve to inform acute risk management decisions.